Increasing Aircraft Carrier Forward Presence Changing the Length of the Maintenance Cycle - Yardley, Roland J. (RAND Corporation, 2008)
The U.S. Navy's aircraft carrier fleet must meet the forward presence requirements of theater commanders. With a decreasing fleet size, planners must balance the timing of maintenance, training, and deployment with presence and surge demands. Evaluating multiple one- and two-deployment scenarios per cycle, RAND examines the feasibility of different cycle lengths, their effect on carrier forward presence, and their impact on shipyard workloads.